Responses of Blood Metabolites and Proteins to Different Vitamin A Levels in Korean Native Steers - Wang, Tao; Lee, Kyung-Hoon; Jung, U-Suk; Jin, Yong-Cheng; Lee, Sang-Bum; Lee, Jae-Sung; Hwang, Jin-Hee; Lim, Ji-Na; Kim, Min-Jeong; Choi, Seong-Ho; Choi, Man-Ho; Lee, Hong-Gu (UNIV AGRICULTURE, FAC VETERINARY SCIENCE, 2014)
This study was conducted to determine the correlation between vitamin A restriction and serum metabolites as well as global proteins expression. Forty-eight animals were randomly divided into three groups and given different vitamin A supplementation: High (4.8 IU/g feed), Medium (2.43 IU/g feed) and Low (1.14 IU/g feed). Blood was collected individually via the external jugular veins. Results showed that the concentrations of Ca, total cholesterol, cortisol and cortisone, and the activity of 11beta-hydroxysteroid dehydrogenase (11-HSD) type 2 varied among the groups. An up-regulated (hibernation protein 25) and four down-regulated proteins (gelsolin a, alpha-1-microglobulin/ bikunin precursor, transthyretin, and complement factor B) were identified in a proteomics study. These data demonstrated that vitamin A deficiency had considerable effects on the serum levels of several metabolites and global proteins expression and these metabolites and proteins may be used as physiological markers in the study of adipogenic differentiation prevention by vitamin A. (C) 2014 PVJ. All rights reserved
Keywords: COMPLEMENT FACTOR B; MACULAR DEGENERATION; PLASMA; ALPHA(1)-MICROGLOBULIN; TRANSTHYRETIN; RESTRICTION; ACID